The 11 September Attacks and the Fourth Wave 2.0 of International Terrorism - Ario Bimo Utomo (UIN Raden Mas Said Surakarta, 2019)
The 11 September attacks in 2001 were one of the most shocking incidents within the post-Cold War era. Moreover, its location which happened in the United States can also be translated as a symbolic warning for the liberal world order, signifying that security remains a salient topic even after the â€œEnd of Historyâ€ postulated by Fukuyama. This article examines whether the 11 September attacks has changed the course of international relations. In so doing, I attempt to use â€œthe waves of terrorismâ€ as a framework to understand the development of different stages of terrorism. The method that I used was desk research based on sources such as official reports, previous studies on terrorism, and classic literature on international security. This article finds that the 11 September attack serves as a game-changer in international relations as it unveils the new face of the religious wave of. First, the attacks ignited a refined version of the religious wave by employing information technology, making it even more sporadic and unpredictable. Second, it reshapes international security by shifting away from the state-centric narrative, putting the terrorists as new international actors. Third, it has altered the security relations of the United States with other countries, creating new global polarisations.